Per Oral Endoscopic Myotomy for Zenker's Diverticulum: A Novel and Superior Technique Compared With Septotomy?. Issue 3 (25th March 2022) - Kahaleh, Michel; Mahpour, Noah Y.; Tyberg, Amy; Bareket, Romy; Shahid, Haroon M.; Sarkar, Avik; Abdelqader, Abdelhai; Gjeorgjievski, Mihajlo; Marino, Daniel; Kats, Daniel; Gaidhane, Monica; Greenberg, Ian; et al.
Abstract : Introduction: Endoscopic management of Zenker diverticuli (ZD) has traditionally been via septotomy technique. The recent development of tunneling technique has shown to be both efficacious and safe. The aim of this study is to evaluate the tunneling technique using per oral endoscopic myotomy (Z-POEM) versus septotomy. Methods: Patients who underwent endoscopic management of ZD either by Z-POEM or septotomy from March 2017 until November 2020 from 9 international academic centers were included. Demographics, clinical data preprocedure and postprocedure, procedure time, adverse events, and hospital length of stay were analyzed. Results: A total of 101 patients (mean age 74.9 y old, 55.4% male) were included: septotomy (n=49), Z-POEM (n=52). Preprocedure Functional Oral Intake Scale score and Eckardt score was 5.3 and 5.4 for the septotomy group and 5.9 and 5.15 for the Z-POEM group. Technical success was achieved in 98% of the Z-POEM group and 100% of the septotomy group. Clinical success was achieved in 84% and 92% in the septotomy versus Z-POEM groups. Adverse events occurred in 30.6% (n=15) in septotomy group versus 9.6% (n=5) in the Z-POEM group ( P =0.017). Reintervention for ongoing symptoms occurred in 7 patients in the septotomy group and 3 patients in the Z-POEM group. Mean hospital length of stay was shorter for the Z-POEM group, at 1.5 versus 1.9 days. Conclusions: A tunneling technique via the Z-POEM procedure is an efficacious and safe endoscopic treatment for ZD. Z-POEM is a safer procedure with a statistically significant reduction in adverse events compared with traditional septotomy technique.